Minimally invasive micro-sclerostomy (MIMS): a novel approach to lowering intraocular pressure and reducing medication burden - Popowska, Monika; Lazicka-Galecka, Monika; Dziedziak, Jacek; Galecki, Tomasz; Kaminska, Anna; Izdebska, Justyna; Szaflik, Jacek Pawel (Klinika Oczna / Acta Ophthalmologica Polonica, 2026)
Minimally invasive micro-sclerostomy (MIMS) is a novel ab interno filtration technique designed to lower intraocular pressure (IOP) in patients with open-angle glaucoma (OAG) without requiring permanent implants. This study aimed to assess the one-year efficacy and safety of MIMS in individuals with medically uncontrolled OAG. Seventeen eyes of 17 patients underwent MIMS with intraoperative mitomycin C (0.3 mg/ml) application. No implants or stents were used. Patients were followed for 12 months. Primary outcomes included mean IOP reduction and change in the number of antiglaucoma medications. Secondary outcomes comprised complete and qualified surgical success, the rate of medication independence, and postoperative complications. At baseline, the mean IOP was 20.5 ±3.5 mmHg, decreasing to 16.0 ±6.6 mmHg at 12 months (22% reduction; p = 0.0019). The number of medications decreased from 2.7 ±0.9 to 0.71 ±0.99 (74% reduction; p < 0.001). Complete surgical success (IOP ≤ 18 mmHg, ≥ 20% reduction, no medication) was achieved in 41.2% of eyes, qualified success (same IOP criteria with or without medication) in 58.8%. Medication independence was noted in 58.8%. No intraoperative complications occurred. Transient iris occlusion was observed in 17.6% of eyes and managed conservatively. These results suggest that MIMS is a safe and effective, implant-free option for reducing IOP and medication burden in OAG patients. Further controlled studies are warranted to validate its clinical utility.